Broken Heart Syndrome: Takotsubo Cardiomiopathy After Intraoperative Rupture of Intracranial Aneurysm - Ralha, Tânia; Raimundo, Ana (Journal of the Portuguese Society of Anesthesiology, 2015)
Patients with aneurysmal subarachnoid haemorrhage can display several cardiacmanifestations whose differential diagnosis is challenging, especially in the intraoperativeperiod. Takotsubo’s cardiomyopathy is a rare disturbance, occurring witha frequently reversible left ventricular dysfunction and showing electrocardiographicchanges that mimic an acute coronary syndrome. The following describes the caseof a 41 year old woman with an aneurysmal rupture during the clipping of a giantaneurysm of the left anterior cerebral artery, followed by electrocardiographic andlaboratorial changes suggesting myocardial ischemia. She developed a progressiveleft ventricular dysfunction without relation with cardiac enzymology, leadingto cardiogenic shock, secondary cerebral ischemia and brain death. There are fewreports of Takotsubo incidents in the intraoperative context. The anaesthesiologistshould be alert to this syndrome due to the clinical requirements which demand thesimultaneous handling of two intraoperative emergencies; a delay in the diagnosiscan defer proper treatment and influence prognosis.